ADSORBENT MATERIALS FOR EMERGING CONTAMINANT (TETRACYCLINE) REMOVAL - Serrato, Denisse Morales; Pérez, Jonatan Torres; Baltazar, Álvaro de Jesús Ruíz; López, Simón Yobanny Reyes (International Journal of Research -GRANTHAALAYAH, 2021)
Water pollution is a serious environmental problem caused by activities. A group of pollutants that are not controlled in the environment but that cause harmful effects on the ecosystem are known as emerging pollutants. One of these groups of emerging pollutants detected in water bodies are pharmaceutical compounds. One of the main problems caused by pharmaceutical compounds as pollutant is bacterial resistance. are a family of antibiotics frequently used. Due to their poor absorption they are released into the environment through feces and urine as active ingredients. Wastewater treatment consists in three stages: primary, secondary, and tertiary treatment. Tertiary treatment employs methods such as reverse osmosis, oxidation-reduction, ultraviolet irradiation, and adsorption. Adsorption is used because it is a simple and effective. For the choice of an effective adsorbent material, surface area, porosity, adsorption capacity, mechanical stability, and factors such as profitability, regeneration, sustainability, and selectivity are considered. In the present review, the adsorbents commonly used in the treatment of water contaminated with were analyzed. The adsorbents used have been classified in a general way as metallic materials, polymers, ceramics, composites, and materials based on biomass.